Mediación laboral y su impacto en las relaciones colectivas de trabajo en Perú - Cadillo Ángeles, Carlos (2019)
The present article analyzes the impact of labour conflict mediation in work relationships in Peru and how this alternative dispute resolution instrument is an ideal way to solve problems. That is why this article analyze the importance of labour mediation in the conflicts that arise between employers and workers. The author seeks to explain why it is necessary to revalue labour conflict mediation and return to the original meaning, because it represents a tool through which parties may resolve problems in a peaceful way.